Let's do the long division
color(white)(aaaa)aaaa n^3+2n^2-5n+12n3+2n2−5n+12color(white)(aaaa)aaaa∣∣n+4n+4
color(white)(aaaa)aaaa n^3+4n^2n3+4n2color(white)(aaaaaaaaaaaaa)aaaaaaaaaaaaa∣∣n^2-2n+3n2−2n+3
color(white)(aaaaa)aaaaa 0-2n^2-5n0−2n2−5n
color(white)(aaaaaaa)aaaaaaa -2n^2-8n−2n2−8n
color(white)(aaaaaaaaaaa)aaaaaaaaaaa 0+3n+120+3n+12
color(white)(aaaaaaaaaaaaa)aaaaaaaaaaaaa +3n+12+3n+12
color(white)(aaaaaaaaaaaaaaa)aaaaaaaaaaaaaaa +0+0+0+0
So, the remainder is =0=0 and the quotient is =n^2-2n+3=n2−2n+3
If we use the remainder theorem
f(n)= n^3+2n^2-5n+12f(n)=n3+2n2−5n+12
f(-4)=-64+32+20+12=0f(−4)=−64+32+20+12=0
The remainder is =0=0